“Smart-Bung” Pengembangan Media Pembelajaran Pada Teknik Dasar Bulutangkis - Debian Solekhudin (YLPK Mahardhika, 2022)
This research is motivated by the lack of interesting learning media innovations that exist for learning PJOK, especially about basic badminton techniques and the difficulty of some students in understanding the basic badminton techniques taught in schools due to the lack of student interest in learning PJOK, especially badminton when in class or learning theory. . This study aims to develop a learning application for the basic techniques of badminton